First Nations women's experiences with perinatal care in Northern Manitoba - Brownell, Emily (2024)
Problem: First Nations women living in rural or remote communities in Canada are often required to leave their communities for perinatal care due to Health Canada’s Evacuation Policy. Forced evacuation disrupts traditional birthing practices and knowledge transfer and has numerous adverse effects on First Nations women, children, families, and communities. In Northern Manitoba, a large proportion of First Nations women have to travel more than two hours to give birth, and many experience a lack of choice regarding their perinatal health care, while the care available is often fragmented and culturally unsafe. Methods: This study was guided by a Two-Eyed Seeing framework and utilized Sharing Circles, an Indigenous practice used in research. I gathered the stories of First Nations mothers and Elders from Northern Manitoba as they shared their experiences of accessing care during the perinatal period. I also gathered their recommendations for changes to the perinatal care system in Northern Manitoba. Due to feasibility issues, most participants shared their stories in a one-on-one, conversational method. Results: Two mothers and three Elders from Northern Manitoba shared their stories and experiences with perinatal care. The women who were able to utilize traditional birthing practices spoke positively of these experiences, while the experiences shared about the Western medical system were largely negative. The participants also shared teachings, recommendations, and advice for First Nations mothers and for changes that can be made to the perinatal care system in Northern Manitoba to better support First Nations women and deliver more appropriate, culturally safe care. Conclusions: The perinatal care experience of many First Nations women in Northern Manitoba continues to be defined by lack of choice, communication, and support, long periods of forced travel away from community resulting in isolation and disconnection, and experiences of racism and culturally unsafe care. In order for perinatal care to be ...